Adsorptive Removal of Copper (Cu) in Sasirangan Liquid Waste by Utilization of Rice Husk as Activated Carbon - Syauqiah, Isna; Nurandini*, Desi; Prihatini, Nopi Stiyati; Jamiyaturrasyidah, Jamiyaturrasyidah (Graduate School of Universitas Syiah Kuala, 2023)
- The business of sasirangan - the conventional texture of Banjar Tribe - has been one of the superb items of South Kalimantan. Sasirangan creation in the shading system utilizes many synthetic components containing weighty metals, which is and its waste possibly dirties the climate. One weighty metal squanders copper (Cu), poisonous to sea-going living beings and people. The treatment for Sasirangan modern wastewater should be possible by an adsorption cycle that utilizations enacted carbon as an adsorbent. This study intends to decide the capacity of enacted carbon produced using rice husk to adsorb Cu from sasirangan fluid burn by dissecting the impact of contact time and adsorbent dose on the adsorption interaction. The bunch framework led the activity with substance and actual actuation. Synthetic initiation was finished by dousing the enacted carbon of rice husk with HCl answer for 24 hours. Simultaneously, actual enactment was done by consuming a heater at 500C for 2 hours. The adsorption treatment was given on sasirangan burn through examples with varieties in contact time (30, 60, and 120 minutes) and the adsorbent portion (2, 4, and 6 grams). The highest productivity of contained Cu decrease is 72.34% utilizing carbon with initiation. The ideal contact time expected in the adsorption cycle of weighty metal Cu in Sasirangan liquid waste is 120 minutes, with the ideal portion of 4 grams of actuated rice husk carbon adsorbent.